(untitled) (Comprehensive Journal of Science, 2025)
German policy towards the end of the nineteenth century and the beginning of the twentieth century was concentrated on the Mediterranean Sea, especially with the escalation of the international political and military conflict within Europe. From this perspective, Germany decided to cooperate with certain local powers hostile to the states colonizing them, and Libya was among those countries. Libya’s geostrategic and geopolitical location distinguished it with an importance that made it the focus of attention for the major powers at the time. This importance led Germany to place its full political and military weight in the Mediterranean basin and in Libya, considering it the bridge leading to Egypt and the connecting line between the North African states, in addition to its significance for the opposite European shore. This study focuses on researching German policy towards Libya during this critical phase, specifically the period 1914–1918. It examines the patterns Germany adopted in its political approach, such as its declaration of neutrality regarding the Libyan issue in 1911, the date of the Italian invasion and colonization of Libya, despite the fact that they were previously allies. However, political necessity dictated that Germany work towards protecting and achieving its own interests, which is why it maintained neutrality and took into account the presence of the Ottoman Empire as a third party in the matter. In the same context, this study seeks to shed light on the German political stance on the Libyan Jihad movement against Italian colonialism, in an attempt to understand the motives behind it and, at the same time, explore the goals it sought to achieve on another front. German political interest in Libya was significant during World War I (1914–1918), a critical and dangerous phase for all conflicting powers, whether local or colonial. Libya became an important location for the docking of German submarines, both those carrying aid to the Libyan Mujahideen and those military ones attacking British forces off the Egyptian coast. This study will rely on primary sources represented by documents found in the German Political Archive and the Ottoman Archive, in addition to various sources and references covering aspects of this topic.